Repeated Cross-Sectional Survey of Ectoparasites in Sheep from Central Tunisia: Does Low Prevalence Indicate Good Hygiene or Resistance to Ectoparasites? - Elati, Khawla; Daly, Nesrine; Dhibi, Mokhtar; Laaribi, Hela; Rekik, Mourad; Gharbi, Mohamed (MDPI, 2024)
Sheep ectoparasites such as chewing lice, fleas and ticks are serious constraints to sheep productivity and are the cause of skin lesions in animals that decrease their market value. This study aims at investigating the ectoparasite fauna infesting small ruminants in the district of Sidi Bouzid (central Tunisia). A total of 1243 Barbarine and Queue Fine de l’Ouest (QFO) sheep were examined every two months for one year. Of the total animals examined, 74 were infested by at least 1 parasite group (5.95%). Three ectoparasite groups were identified as Psoroptes ovis (0.48%; 6/1243), ticks (5.3%; n = 66/1243) and one specimen of Ctenocephalides canis (0.08%; n = 1/1243). The most abundant tick among the 358 specimens was Rhipicephalus sanguineus sensu lato (n = 337; 94.1%), followed by Hyalomma impeltatum (n = 7/358; 1.9%), H. dromedarii (n = 7/358; 1.9%), H. excavatum (n = 5/358; 1.4%) and only two specimens of H. scupense (n = 2/358; 0.55%). The sheep herds showed low infestation prevalence by ectoparasite over the year, with a significant difference according to the seasons (p < 0.05). A higher infestation prevalence was recorded in March (14.36%). Barbarine sheep breed showed significantly higher infestation prevalence (16.8%) compared to QFO (0.8%) (p < 0.01). There were no differences in infestation prevalence according to sex of the animal or age groups. Knowledge of the ectoparasite population harboured by sheep, its activity dynamics and risk factors is required to develop effective ectoparasite control options. The low prevalence of ectoparasite infestation in sheep reported here may be due to possible genetic resistance or simply to successful hygiene measures implemented by farmers.